Predictors of increased affective symptoms and suicidal ideation during the COVID-19 pandemic: results from a large-scale study of 14 271 Thai adults - Jing Li; Marco Solmi; Bo Zhou; Michael Maes; Trevor Thompson; Christoph Correll; Sorawit Wainipitapong; Thitiporn Supasitthumrong; Chavit Tunvirachaisakul; Teerayuth Rungnirundorn; Anchalita Ratanajaruraks; Chaichana Nimnuan; et al. (BMJ Mental Health, 2024)
Background Increasing data suggest emergent affective symptoms during the COVID-19 pandemic.Objectives To study the impact of the COVID-19 pandemic on affective symptoms and suicidal ideation in Thai adults.Methods The Collaborative Outcomes Study on Health and Functioning during Infection Times uses non-probability sampling (chain referring and voluntary response sampling) and stratified probability sampling to identify risk factors of mental health problems and potential treatment targets to improve mental health outcomes during pandemics.Findings Analysing 14 271 adult survey participants across all four waves of the COVID-19 pandemic in Thailand, covering all 77 provinces from 1 June 2020 to 30 April 2022, affective symptoms and suicidality increased during COVID-19 pandemic. Affective symptoms were strongly predicted by pandemic (feelings of isolation, fear of COVID-19, loss of social support, financial loss, lack of protective devices) and non-pandemic (female sex, non-binary individuals, adverse childhood experiences (ACEs), negative life events, student status, multiple mental health and medical conditions, physical pain) risk factors. ACEs, prior mental health conditions and physical pain were the top three risk factors associated with both increased affective symptoms and suicidal ideation during the COVID-19 pandemic. Partial least squares analysis showed that ACEs were the most important risk factor as they impacted most pandemic and non-pandemic risk factors.Clinical implications Rational policymaking during a pandemic should aim to identify the groups at highest risk (those with ACEs, psychiatric and medical disease, women, non-binary individuals) and implement both immediate and long-term strategies to mitigate the impact of ACEs, while effectively addressing associated psychiatric and medical conditions.